The Effect of Transformational Leadership on Innovative Work Behavior Mediated by the Organizational Culture - Ariana Fibriandhini; Surati Surati; Hermanto Hermanto (Postgraduate, University of Mataram, 2022)
Innovative work behavior, transformational leadership style and organizational culture are critical variables that must be the focus of attention of every organization in order to succeed in this era of rapid technological change. This study aims to determine the effect of transformational leadership on innovative work behavior that is mediated by the organizational culture of Madrasah Aliyah Negeri (MAN) teachers throughout the city of Mataram. The population of this research is active teachers in MAN in Mataram City, amounting to 124 teachers. The rate of return of questionnaires in this study was 83% or a total of 124 respondents. Hypothesis testing in this study uses path analysis with the SmartPLS3.2.8 program. The results showed that transformational leadership has a positive and significant effect on innovative work behavior, transformational leadership has a positive and significant effect on organizational culture, organizational culture has a positive and significant effect on innovative work behavior, transformational leadership has a positive and significant effect on innovative work behavior mediated by culture organizations where organizational culture acts as a partial mediating variable. These findings indicate that to improve innovative work behavior it is necessary to apply transformational leadership styles and strengthen organizational culture